Static Bending Analysis of Auxetic Plate by FEM and a New Third-Order Shear Deformation Plate Theory - Cong, Pham Hong; Phuc, Pham Minh; Thiem, Hoang Thi; Manh, Duong Tuan; Duc, Nguyen Dinh (VNU Journal of Science: Natural Sciences and Technology; Vol 36 No 1DO - 10.25073/2588-1140/vnunst.5000, 2020)
In this paper, a finite element method (FEM) and a new third-order shear deformation plate theory are proposed to investigate a static bending model of auxetic plates with negative Poisson’s ratio. The three – layer sandwich plate is consisted of auxetic honeycombs core layer with negative Poisson’s ratio integrated, isotropic homogeneous materials at the top and bottom of surfaces. A displacement-based finite element formulation associated with a novel third-order shear deformation plate theory without any requirement of shear correction factors is thus developed. The results show the effects of geometrical parameters, boundary conditions, uniform transverse pressure on the static bending of auxetic plates with negative Poisson’s ratio. Numerical examples are solved, then compared with the published literatures to validate the feasibility and accuracy of proposed analysis method.